Is it efficient to single-handedly run a multi-machine harvesting operation? A case study from the Northeast United States. Issue 3 (1st September 2016) - Kelly, Matthew C.; Germain, René H.
ABSTRACT: Harvest operations carried out by a single logger operating more than one machine are common, yet little is understood of their productivity and costs. A case study of three single-logger operations (SLO) located in New York, USA was conducted to assess their harvest costs and productivity. Daily activity and production data were collected from each harvest operation and analyzed in conjunction with machine rate calculations to estimate system productivity and costs for each SLO. Based on these data, deterministic simulations were conducted to assess how the addition of second and third loggers affected harvest system efficiency. Operator and equipment utilization rates were calculated at the systems level and compared among the observed SLOs and simulated two- and three-logger simulations. In most cases, the introduction of additional loggers reduced operator utilization due to the introduction of system delays, and therefore, increased labor costs. However, this investment in labor often led to greater equipment utilization and lower production costs. Overall, system productivity increased by between 77% and 145% when additional loggers were added to the system, while costs per cubic meter (m 3 ) decreased by as much as 28%. The results of this study will inform business decisions regarding the efficiency of SLO and the potential gains associated with investing in crew sizes greater than one.